The NLRP3 inflammasome recognizes alpha-2 and alpha-7.3 giardins and decreases the pathogenicity of Giardia duodenalis in mice - Panpan Zhao; Jianhua Li; Xin Li; Jingquan Dong; Xiaocen Wang; Nan Zhang; Shan Li; Min Sun; Xichen Zhang; Zhibang Wang; Min Liang; Ying Li; et al. (Parasites & Vectors, 2023)
Abstract Background Giardia duodenalis is a parasitic organism that can cause giardiasis, an intestinal infection, particularly prevalent in young children, with clinical symptoms of diarrhea. We previously reported that extracellular G. duodenalis triggers intracellular nucleotide-binding oligomerization-like receptor 3 (NLRP3) inflammasome activation and regulates the host inflammatory response by secreting extracellular vesicles (EVs). However, the exact pathogen-associated molecular patterns in G. duodenalis EVs (GEVs) involved in this process and the role of the NLRP3 inflammasome in giardiasis remain to be elucidated. Methods Recombinant eukaryotic expression plasmids of pcDNA3.1(+)-alpha-2 and alpha-7.3 giardins in GEVs were constructed, transfected into primary mouse peritoneal macrophages and screened by measuring the expression levels of the inflammasome target molecule caspase-1 p20. The preliminary identification of G. duodenalis alpha-2 and alpha-7.3 giardins was further verified by measuring the protein expression levels of key molecules of the NLRP3 inflammasome (NLRP3, pro-interleukin-1 beta [IL-1β], pro-caspase-1, and caspase-1 p20), the secretion levels of IL-1β, the level of apoptosis speck-like protein (ASC) oligomerization and the immunofluorescence localization of NLRP3 and ASC. The roles of the NLRP3 inflammasome in G. duodenalis pathogenicity were then evaluated using mice in which NLRP3 activation was blocked (NLRP3-blocked mice), and body weight, parasite burden in the duodenum and histopathological changes in the duodenum were monitored. In addition, we explored whether alpha-2 and alpha-7.3 giardins triggered IL-1β secretion in vivo through the NLRP3 inflammasome and determined the roles of these molecules in G. duodenalis pathogenicity in mice. Results Alpha-2 and alpha-7.3 giardins triggered NLRP3 inflammasome activation in vitro. This led to caspase-1 p20 activation, upregulation of the protein expression levels of NLRP3, pro-IL-1β and pro-caspase-1, significant enhancement of IL-1β secretion, ASC speck formation in the cytoplasm and also induction of ASC oligomerization. Deletion of the NLRP3 inflammasome aggravated G. duodenalis pathogenicity in mice. Compared to wild-type mice gavaged with cysts, mice gavaged with cysts in NLRP3-blocked mice displayed increased trophozoite loads and severe duodenal villus damage, characterized by necrotic crypts with atrophy and branching. In vivo assays revealed that alpha-2 and alpha-7.3 giardins could induce IL-1β secretion through the NLRP3 inflammasome and that immunization with alpha-2 and alpha-7.3 giardins decreased G. duodenalis pathogenicity in mice. Conclusions Overall, the results of the present study revealed that alpha-2 and alpha-7.3 giardins trigger host NLRP3 inflammasome activation and decrease G. duodenalis infection ability in mice, which are promising targets for the prevention of giardiasis. Graphical Abstract